1995
DOI: 10.1002/hep.1840210130
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the fenestrae-associated cytoskeleton of rat liver sinusoidal endothelial cells

Abstract: This article describes the cytoskeleton associated with fenestrae and sieve plates of rat liver sinusoidal endothelial cells. Fenestrae control the exchange between the blood and parenchymal cells. We present evidence indicating that several agents that change the fenestrae and sieve plates also cause changes in the cytoskeleton. Cultured liver endothelial cells (LECs) were slightly fixed and treated with cytoskeleton extraction buffer. Detergent-extracted whole mounts of cultured cells were prepared for eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
120
2
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 20 publications
9
120
2
1
Order By: Relevance
“…24 The effect of sodium decanoate on the size of sinusoidal fenestrae may be mediated by modulation of the fenestrae associated cytoskeleton, which has been shown to be involved in regulating the size of fenestrae. 25 Administration of the Kupffer cell blocking agent GdCl 3 or higher viral doses in New Zealand White and Fauve de Bourgogne rabbits only partially overcome the effect of the anatomical barrier constituted by the small fenestrae. A longer circulation time of adenoviral vectors secondary to reduced Kupffer cell phagocytosis or a higher vector dose will allow more vectors to penetrate into the space of Disse via fenestrae with a sufficient diameter for passage of adenoviral vectors.…”
Section: Discussionmentioning
confidence: 99%
“…24 The effect of sodium decanoate on the size of sinusoidal fenestrae may be mediated by modulation of the fenestrae associated cytoskeleton, which has been shown to be involved in regulating the size of fenestrae. 25 Administration of the Kupffer cell blocking agent GdCl 3 or higher viral doses in New Zealand White and Fauve de Bourgogne rabbits only partially overcome the effect of the anatomical barrier constituted by the small fenestrae. A longer circulation time of adenoviral vectors secondary to reduced Kupffer cell phagocytosis or a higher vector dose will allow more vectors to penetrate into the space of Disse via fenestrae with a sufficient diameter for passage of adenoviral vectors.…”
Section: Discussionmentioning
confidence: 99%
“…This is believed to be accomplished by adjusting the diameter and/or number of fenestrae via an actin-based contraction system. 13,16,17 Compelling data from several laboratories have documented the exquisite zonal variation of sinusoidal porosity as a function of fenestration diameter and number along the portal-central axis of the lobule. 9,23-25 In FIG.…”
Section: Discussionmentioning
confidence: 99%
“…(See also vitro and in vivo studies have also shown that fenestrae can modulate their diameter in response to soluble agents as well as a variety of environmental conditions, including changes in shear stress and portal pressure, and pathological ECM deposition. [10][11][12][13][14][15][16][17][18][19] We sought to investigate the trends in porosity expression in the SEC within and between lobule zones throughout the revascularization process following PHx. We believed that such changes may play a critical role in the sieving function of the sinusoids and contribute to the progression of the regenerative process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver sinusoidal endothelial cells (LSECs) play important roles in regulating hepatic sinus function. LSECs line the capillaries of the microvasculature and possess fenestrae that facilitate filtration between the liver parenchyma and sinusoids by serving as a selectively permeable barrier (Braet et al 1995. Results have indicated that NAFLD is associated with dysfunction of LSECs .…”
Section: Introductionmentioning
confidence: 99%